Security market investment and decision making in buying shares: a case study on Kelantanese investors / Rogayah Mohd Rali - Mohd Rali, Rogayah (2003)
The research title is "Security Market Investment and Decision Making in Buying Shares: Study on Kelantanese Investors". This research is carried out to explore the factors that influence investment decision-making by the investors, how far their level of knowledge on certain factors such as financial terms or aspects; internal and external factors might affect the investor in making their investment decision, and beliefs on the past experience. It is also to see how likely the investors obtain profits based on the factors that influenced them in making investment decision. Researcher is using the primary data and secondary data. This study involves 100 individual investors in KB Securities Sdn Bhd. For this purpose, researcher used questionnaires to collect the data from the respondents. There are 46 questions used. The data collected were analyzed using the SPSS program by using the Frequency and Chi-Square test. The overall result from the study shows, there are eight factors that influence the investors in making investment decision, and the factor that most influenced investors in making their investment decision is the company financial performance. Then, most of the investors are familiar and understands towards the financial statement of the company, which include the financial items (company annual report, Profit and Loss account and others). The result also shows that Malaysian political situation are most influenced the performance of local stock market. And then, the investors are relied on company performance in making the investment decision. The result also shows that most of the investors seldom make a profit based on the factors above. The investors obtain knowledge on investment is from their reading. And lastly, for the hypothesis testing, it show there is a significant relationship between making the right decision (get profit) and the factors of Top Ten counter active of the day, Right and bonus issue, and company financial performance.